Partially encased columns eon wall under fire from one side - Piloto, P.A.G. (2019)
The steel columns have a great loadbearing capacity, however when exposed to fire conditions are heated in a relatively short period. The steel-concrete composite columns consist in an excellent alternative solution to bare steel column. Partially Encased Columns (PEC) have higher strength and stiffness when compared to steel bare profiles in fire conditions. The fire resistance of the PEC depends on the temperature evolution in each material and component, being this temperature field affected by the protection effect of the wall.